Corporate Governance Country Assessment : Colombia - World Bank (Washington DC, 2013)
This report assesses the corporate governance policy framework, enforcement and compliance practices in Colombia. The capital markets are small relative to the economy and trading volume is low. The corporate sector is largely owned and controlled by family groups and conglomerates. The challenge is to create an environment where medium-sized companies can raise capital in the market and help them make the transition from tightly-controlled family firms to public companies. While pension funds represent a large and rapidly growing source of funds, they are reluctant to invest in equities. It has been demonstrated across countries that capital market development correlates positively with the degree of shareholder protection and good corporate governance. Awareness of the importance of corporate governance issues is growing. Success stories of privatizations linked with good corporate governance highlight the importance of the issue. Colombia is an interesting example of the interplay between legal changes and voluntary initiatives based on the incentive to attract capital. It has put a minimum corporate governance disclosure regime in place for companies that wish to be eligible for pension fund investments. The report makes policy recommendations that may be grouped under three broad headings: legislative reform, institutional strengthening and voluntary/private initiatives. The report recommends (1) adopting a securities bill as proposed by the securities regulator Supevalores; (2) adopting international standards and creating an independent audit oversight board; (3) improving enforcement; (4) enhancing compliance monitoring with the code of good governance; and (5) creating a director training organization.